Comparison and evaluation of percutaneous transforaminal endoscopic discectomy treatment efficacy in patients with lumbar disc herniation of different age groups - Xu, Xiulei; Song, Jie; Zhou, Gang; Li, Jun; Zhang, Xiaorui (Frontiers in Surgery, 2025)
BackgroundLumbar disc herniation (LDH) is also a degenerative disease of the spine, and age is an important factor affecting the prognosis of LDH patients. The aim of this study is to analyze the pain levels and physical function changes of LDH patients in different age groups before and after percutaneous transforaminal endoscopic discectomy (PTED) treatment, and to analyze the factors that affect postoperative clinical outcome indicators.MethodThis study included 100 LDH patients. Collect baseline characteristics of patients and compare the differences in pain levels, ODI scores, JOA scores, BBS scores, and SF-36 scores between LDH patients of different ages before and after PTED treatment. The generalized linear mixed model (GLMM) was used to analyze the impact of different factors on postoperative clinical outcomes, and the ROC curve was used to evaluate the predictive ability of age on postoperative indicator improvement.ResultThe research results indicate that after PTED treatment, the postoperative clinical outcomes of all patients have significantly improved, with the younger group showing the most significant improvement. In the young group, the amount of intraoperative bleeding, the length of operation, the length of postoperative bed rest, and the incidence rate of postoperative complications were the lowest. GLMM analysis showed that follow-up time, Pfirrmann grading, baseline NLR level, age, lumbar spondylolisthesis, affected intervertebral disc segment L5/S1, and the interaction between age and follow-up time were significant influencing factors for postoperative clinical outcomes. As the follow-up time prolongs, the influence of age on ODI and JOA gradually weakens. ROC curve analysis showed that age had the strongest predictive ability for the improvement of preoperative and postoperative ODI scores and JOA scores, with AUC values of 0.641 and 0.646, respectively.ConclusionThe clinical outcomes of PTED treatment in young patients showed the most significant improvement. With the extension of postoperative follow-up time, the influence of age on postoperative clinical outcomes gradually decreases. This study also provides valuable reference for exploring the factors that affect the therapeutic effect of PTED.